A Novel Virtual Coaching System Based on Personalized Clinical Pathways for Rehabilitation of Older Adults—Requirements and Implementation Plan of the vCare Project - Kyriazakos, Sofoklis; Schlieter, Hannes; Gand, Kai; Caprino, Massimo; Corbo, Massimo; Tropea, Peppino; Judica, Elda; Sterpi, Irma; Busnatu, Stefan; Philipp, Patrick; Rovira, Jordi; Martínez, Alvaro; et al. (Frontiers in Digital Health, 2020)
Home based rehabilitation after an acute episode or following an exacerbation of a chronic disease is often problematic with a clear lack of continuity of care between hospital and home care. Secondary prevention is an essential element of long-term rehabilitation where strategies oriented towards risk reduction, treatment adherence and optimization of quality of life need to be applied. Frail and sometimes isolated, the patient fails to adhere to the proposed post-discharge clinical pathway due to lack of appropriate clinical, emotional and informational support. Providing a suitable rehabilitation after an acute episode or a chronic disease is a major issue as it helps people to live independently and enhance their quality of life. However, as the rehabilitation period usually lasts some months, the continuity of care is often interrupted in the transition from the hospital to the home. Virtual coaches can help these patients to proceed with a personalized rehabilitation that complies with age-related conditions. These coaches are a key technology for empowering patients through the enhancement of the adherence to the care plan and the prevention of risks. In this paper, we are presenting a novel virtual coaching system that addresses these challenges by combining recent technological advances with clinical pathways, based on joint research and validation activities from researchers from the medical and the ICT domain.